Partnerství veřejného a soukromého sektoru v oblasti sociálních služeb - Sabolová, Veronika (Univerzita Pardubice, 2008)
The article is devoted to the issue of Public Private Partnership and its potential application in the field of social services. In the introduction, is briefly reflected the characteristics of Public Private Partnership (PPP) and are given its basic features. Particular attention is focused on the specifics of using PPP in the field of social services. Finally, is shown that through the application of the principles of PPP can achieve significant savings in public resources.
Keywords: aging population; financing projects; Public Private Partnership; social services